Prefabricación, Transporte y Ensamblaje de la Estructura Metálica de un Tanque de Almacenamiento de Agua Potable para Los Chiles - Núñez-Corrales, Paulo (Instituto Tecnológico de Costa Rica, 2014)
The water supply problem in Costa Rica, lies in the lack of adequate water infrastructure, which prevents us to meet the demand due to population growth as well as commercial, industrial and tourist level. In this paper, the logistic aspects of shop prefabrication, transport and site assembly in a metal tank for water storage of 250 m3 of capacity located in Los Chiles, Alajuela are analyzed. This by analyzing space and equipment limitations both in plan and on-site, determining the level of pre assembly with which the elements would be manufactured and transported and the development of procedures for the execution of the work. In addition, a dynamic seismic analysis of the structure, using models developed in SAP2000, is performed to determine the most characteristic critical points of the structure, to provide general recommendations regarding the frequency and inspection criteria and some of the preventive maintenance actions. The analysis concludes that the best way to manufacture and transport the support structure is by independent elements, while the cylinder into two sections. The procedures established in the assembly manual represented a prerequisite for the analysis and understanding of the assembly process. Additionally, the seismic analysis found that the structural design of the tank is very conservative, therefore the stress values found in the characteristic elements are low.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2014.
Keywords: SAP2000; Soldadura; Protocolo de inspección; Microsoft project 2013; Análisis sísmico